Understanding Gaze and Scrolling Strategies in Text Consumption Tasks - Dumais, Susan; Iqbal, Shamsi (PETMEI 2015, 2015)
Scrolling is an integral part of our everyday computing experience, and many techniques and devices have been developed to enhance scrolling. We have conducted an 18 participant user study to understand how users’ gaze position and scrolling strategies are coordinated. Our data showed that people scrolled within preferred reading regions of the screen. Scrolling patterns were also influenced by document structure, with most scrolling occurring at the intersection between paragraphs, in order to bring new text into the preferred reading region. We conclude with the implications of our findings with a new gaze-enhanced scrolling technique aimed to support behaviors evident in manual scrolling.